Portable wireless yield monitoring system for rice combine - Yahya, Azmi; Oh, Yun Ju; Mohd Isa, Maryam; Abd Aziz, Samsuzana (Faculty of Engineering, Universiti Putra Malaysia, 2012)
A simple, portable, and rugged instrumentation system has been successfully developed and field demonstrated to monitor, measure and record the harvested crop yield and selected machine performance parameters for any rice combines of any makes and models. The complete system comprises of ultrasonics sensors located at the header to measure crop cutting width, microwave solid flow sensor and microwave moisture sensor at the clean grain auger to measure the flow rate and moisture content of the cleaned grains going into the clean grain tank, electromagnetic detector on the grain elevator drive shaft to monitor the grain elevator rotational speed and a DGPS receiver on the console roof to indicate the combine travel speed and geo-position in the field. All measured parameters were made to display in-real time on the touch panel screen of the embedded system on-board the combine for the interest of the combine operator and also made to display in-real time on the monitor of the toughbook at the on-ground base station for the interest of the system controller. Static calibrations on the individual sensors showed excellent measurement linearity having R2 values within 0.9839 to 1.000 ranges. The wireless communication between the embedded system and the toughbook could be sustained to a maximum distance of 140m apart. Site specific variability maps of crop yield, grain moisture content, combine cutting width, combine traveling speed, combine field capacity, and combine field efficiency within the harvested area could be produced from the data obtained with the instrumentation system using any GIS software.